HUBUNGAN KOMPETENSI KEPRIBADIAN GURU PAK DENGAN MORAL SISWA - Cahyana Malau (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2019)
Abstract - this Research Target is to know the Relation of personality Interest Learn the Christian Education with the Moral Student Class XII SMA Country 1 Tarutung Study Year 2018 / 2019. this Research hypothesizing there are relation which are positive and signifikan between personality Interest Learn the Christian Education with the Moral Student Class XII SMA Country 1 Tarutung of Study Year 2018 / 2019. This research use the descriptive quantitative approach and inferensial, with the population all student class of XII SMA Country 1 Tarutung amounting to 210 people by sampel amount to 42 people. Data collected with the enquette closed, with the question amount as much 38 item compiled pursuant to indicator and expert theory which have been tested the validity and reliablity. Result of data analysis indicate that there are relation which are positive and signifikan between personality Interest Learn the Christian Education with the Moral Student Class of XII SMA Country 1 Tarutung of Study Year 2018 / this 2019 matter proved] rcountrtable equal to 0,605 0,304 and tcountttable] equal to 4,806 2,021. Thereby hypothesis sounding: There are Relation between personality Interest Learn with the student moral positively and acceptable signifikan because have been proven empirically.Keyword: Personality Interest, Student Moral